Influencer Attractiveness, Influencer Expertise, and Purchase Intention in Digital Marketing Transformation: A Systematic Review - Arus Reka Prasetia; Nanda Alvi Fauza (Novatio : Journal of Management Technology and Innovation, 2025)
Digital marketing transformation has elevated influencer marketing into a strategic mechanism through which brands shape consumer evaluation and stimulate purchase intention across increasingly platformized environments. Prior broad reviews and recent meta-analyses have mapped influencer marketing and its aggregate effectiveness, yet evidence remains less clear on how influencer attractiveness and influencer expertise operate as analytically distinct source attributes across platform-specific contexts. This systematic review addresses that focused problem by examining how these two attributes are conceptualized and operationalized, how they are associated with purchase intention, which mediating and moderating mechanisms recur most frequently, and how the evidence differs across global and Indonesian contexts. Following PRISMA 2020 and a PICo-based review design, the study searched Scopus, ScienceDirect, Emerald Insight, SAGE Journals, and Springer Nature Link, applied explicit eligibility criteria, and synthesized 95 empirical journal articles published between 2016 and 2025. The findings indicate that the literature is highly concentrated in recent years, dominated by quantitative survey designs, and theoretically anchored primarily in source credibility and related source-evaluation perspectives. Across the included studies, attractiveness appears more visible in visually expressive environments such as Instagram, whereas expertise appears more salient in live commerce and social-commerce settings where consumers require stronger informational assurance. Parasocial interaction, trust, and perceived credibility emerge as the most recurrent explanatory mechanisms, while Indonesian evidence is analytically relevant but still limited in volume. Overall, the review contributes to digital marketing transformation scholarship by showing that isolating attractiveness and expertise from broader credibility bundles yields a more precise, context-sensitive explanation of purchase intention as a platform-contingent and mechanism-mediated outcome.